URGENSI LANDASAN PSIKOLOGI DAN IPTEK DALAM KURIKULUM UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN SEKOLAH DASAR DI ABAD-21 - Renata Dwi Iswanti; Adya Pramudya Dwi Permata Radianty; Nur Fa'izah, Fitri; Sofyan Iskandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Curriculum development in the modern era requires a solid foundation, especially in terms of psychology and science and technology, in order to be able to answer increasingly complex challenges. The purpose of this research is to understand the urgency in the aspects of science and technology in the curriculum, as well as the psychological aspects in education for the sake of improving the quality of learning. This research uses a qualitative method with a literature study approach from various scientific references. The research reveals that psychological aspects play an important role in adjusting learning according to students' developmental stages, needs and traits, as well as in creating an inclusive and innovative learning atmosphere. Meanwhile, the application of knowledge and technology in the curriculum encourages the utilisation of technology to support learning processes that are innovative, creative and in line with the times. The psychology and science and technology-based curriculum can equip learners with 21st century skills such as critical thinking, creativity, communication and collaboration. However, during implementation, there are still obstacles such as lack of infrastructure, training for teachers, and the level of digital literacy. Therefore, continuous innovation is needed in curriculum development to produce excellent graduates who are ready to compete in the global era.